First record of a self-sustaining population of Alpine charr Salvelinus umbla (Linnaeus, 1758) (Actinopterygii, Salmonidae) in Spain - Aparicio, Enric (Graellsia, 2015)
This work reports for the first time in Spain the presence of the non-native salmonid Alpine charr, usually included into Salvelinus alpinus, but recently revised to Salvelinus umbla. The species was found in a high mountain lake in the Pyrenees belonging to the Garonne catchment (Lake Obago, Val d’Aran, province of Lleida). This is probably not a recent introduction since the presence of one species of Salvelinus in some lakes of the Val d’Aran has been known among anglers for a long time, but the species identification was lacking. The distribution of S. umbla in the Val d’Aran appear to be restricted to a very few lakes and it has not spread downstream. En este trabajo se cita por primera vez en España la presencia del salvelino alpino, generalmente incluido en Salvelinus alpinus, pero recientemente revisado como Salvelinus umbla. La especie fue encontrada en un lago de alta montaña de los Pirineos perteneciente a la cuenca del Garona (Estany Obago, Val d’Aran, Lleida). Probablemente no se trata de una introducción reciente ya que la presencia de una especie de Salvelinus en algunos lagos del Valle de Arán ya era conocida entre los pescadores durante mucho tiempo, pero la identificación de la especie no se había realizado. La distribución de S. umbla en el Valle de Arán parece estar restringida a unos pocos lagos y no se ha extendido a los tramos de río aguas abajo.